Neo-processual archaeology: ‘Alive and kicking’. Some thoughts from the Palaeolithic field - Moro Abadía, Oscar; Fernández Martínez, Victor M.; Hernando Gonzalo, Almudena; Domínguez- Rodrigo, Manuel (Complutum, 2008)
Sin resumen